Common fixed point results of Das-Naik and Geraghty types in u-generalized metric spaces - Kadelburg, Zoran; Radenović, Stojan (Sarajevo Journal of Mathematics, 2017)
In this paper, common fixed point results in u-generalized metric spaces of Branciari are deduced under several types of contractive conditions.